Feel Good, Eat Better: The Role of Self-Compassion and Body Esteem in Mothers’ Healthy Eating Behaviours - Noémie Carbonneau (MDPI AG, 2021)
Mothers’ eating behaviours are important to ensure the health and well-being of themselves and their families. Recent research has pointed to self-compassion, defined as extending kindness to oneself in times of perceived inadequacy or general suffering, as a trait associated with healthy forms of eating, such as intuitive eating, and reduced maladaptive forms of eating, such as emotional eating. However, little is known about the psychological mechanism through which self-compassion relates to healthy eating behaviours. This study examined 100 mothers’ levels of self-compassion, body esteem and eating behaviours. Structural equation modelling revealed that self-compassion was positively associated with diet quality and intuitive eating, while being negatively associated with emotional eating. Moreover, these links occurred, in part, due to higher body esteem. This points to a mechanism through which self-compassion may positively contribute to mothers’ healthy eating behaviours. The implications for eating outcomes and women’s health are discussed.